2020
DOI: 10.3897/zse.96.51962
|View full text |Cite
|
Sign up to set email alerts
|

Squalus shiraii sp. nov. (Squaliformes, Squalidae), a new species of dogfish shark from Japan with regional nominal species revisited

Abstract: A new species of deep-water dogfish shark, Squalus shiraiisp. nov., is described herein as endemic to the tropical waters off Southern Japan. This species has been largely misidentified with S. mitsukurii. However, morphological, meristic and morphometric evidence support it to be a separate and undescribed species. Squalus shiraiisp. nov. differs from this species by having body brown in colour dorsally, caudal fin with ventral and dorsal tips markedly tapered and broadly white, dermal denticles uniscuspidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…The haplotype network revealed that S. japonicus, S. edmundsi, and S. grahami did not share haplotypes, unlike S. clarkae and S. mitsukurii, which did. Squalus mitsukurii was originally described in Japan by Jordan and Snyder (1903), and despite identification issues due to morphological character overlapping, this species presents a circumglobal distribution [69], and its occurrence has likely been overestimated [4,70,71].…”
Section: Discussionmentioning
confidence: 99%
“…The haplotype network revealed that S. japonicus, S. edmundsi, and S. grahami did not share haplotypes, unlike S. clarkae and S. mitsukurii, which did. Squalus mitsukurii was originally described in Japan by Jordan and Snyder (1903), and despite identification issues due to morphological character overlapping, this species presents a circumglobal distribution [69], and its occurrence has likely been overestimated [4,70,71].…”
Section: Discussionmentioning
confidence: 99%